Efecto de extractos de Caesalpinia platyloba sobre huevecillos y larvas de Strongyloides gastrointestinales de bovinos del trópico seco - Gamiño Avalos, Omar (Universidad Michoacana de San Nicolás de Hidalgo, 2018)
The objective of the research was to determine the anthelmintic effect of extracts of Caesalpinia platyloba on eggs (Hs) and gastrointestinal Strongyloides larvae of bovines from the dry tropics, in different livestock production units (UPP) (n=20 animals/UPP) located in the municipality of Carácuaro, Michoacán, México. Faecal samples (MF) were collected from cattle and stems and leaves of Caesalpinia platyloba, the MF (150 g animal-1) were subjected to a diagnostic study coprological-parasitic, also, the inhibition test was carried out on Hs hatching and larval migration, the information collected was analyzed using the methodology of generalized linear models and the differences (α=0.05) between treatments were obtained through least squares means. A prevalence of parasitosis of 82.5±37.9% and an average parasitic load of 4025.7±3635.1 Hs g-1 MF (90.3% of CV), was found, same that was reduced (P<0.05) in the animals under the feeding system native grass-forage arboreous vs system based on native grass: 2180.0±279.3 and 5563.8 ± 255.0 Hs g-1 MF, respectively. Among the extracts of Caesalpinia platyloba, the leaf dichloromethane extract caused greater egg mortality of gastrointestinal Strongyloides (60.7 ± 2.7%) vs stem dichloromethane extract (53.3 ± 2.7%). This extract was also noted for its action against Strongyloides larvae: 92.2±5.1% mortality. The consumption of forage of Caesalpinia platyloba in bovines under grazing (native grass) is a viable alternative to reduce gastrointestinal parasitosis in these animals.

El objetivo de la investigación fue determinar el efecto antihelmíntico de extractos de Caesalpinia platyloba sobre huevecillos (Hs) y larvas de Strongyloides gastrointestinales de bovinos del trópico seco, en diferentes unidades de producción pecuaria (UPP) (n=20 animales/UPP) ubicadas en el municipio de Carácuaro, Michoacán, México. Se recolectaron muestras fecales (MF) de bovinos y tallos y hojas de Caesalpinia platyloba, las MF (150 g animal-1) se sometieron a un estudio diagnóstico coprológico-parasitario, además, se realizó la prueba de inhibición en la eclosión de Hs y migración larval, la información recabada se analizó mediante la metodología de los modelos lineales generalizados y las diferencias (α=0.05) entre tratamientos se obtuvieron a través de medias de mínimos cuadrados. Se encontró una prevalencia de parasitosis de 82.5±37.9% y una carga promedio parasitaria de 4025.7±3635.1 Hs g-1 MF (90.3% de CV), mismo que se redujó (P<0.05) en los animales bajo el sistema de alimentación pasto nativo-forraje arboreo vs sistema a base de pasto nativo: 2180.0±279.3 y 5563.8±255.0 Hs g-1 MF, respectivamente. Dentro de los extractos de Caesalpinia platyloba, el extracto diclorometano de hoja provocó mayor mortalidad de huevesillo de Strongyloides gastrointestinales (60.7±2.7%) vs extracto diclorometano de tallo (53.3±2.7%). Este extracto también se destacaó por su acción contra las larvas de Strongyloides: 92.2±5.1% de mortalidad. El consumo de forraje de Caesalpinia platyloba en bovinos bajo pastoreo (pasto nativo) es una alternativa viable para reducir la parasitosis gastrointestinal en estos animales.
Instituto de Investigaciones Agropecuarias y Forestales. Maestría en Producción Agropecuaria
Keywords: info:eu-repo/classification/cti/6; IIAF-M-2018-2001; Pecuaria; Especies arbóreas; Forraje nutraceútico; Extractos vegetales; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6607